Comparison of cardiorespiratory endurance, body mass index, and learning achievement of students Junior High Schools - Keysha Azhalia Wahono; Oce Wiriawan; Taufiq Hidayat; Sapto Wibowo; Heryanto Nur Muhammad; Mochamad Ridwan (Sriwijaya Journal of Sport, 2025)
Research Problems: Student achievement while studying at school is often seen from test scores, but other factors such as physical fitness and body composition support student academic achievement. Research Objectives: This research identified the level of cardiorespiratory endurance, body mass index, and physical education learning outcomes in students at Government Schools and Private Schools. Methods: Quantitative research involved 68 students consisting of 31 boys and 37 girls aged 13-14. This research instrument was height, weight, and the PACER Test. Data were analysed using Independent Sample T-test, Pearson Correlations, and Multiple Regression Analysis. Results: There’s relationship between BMI and physical education learning outcomes of male student at SMP Negeri. There’s no relationship both BMI and PACER Test to physical education learning outcomes. The three variables contributed 21.8% to this research. Conclusion: The better the BMI category, physical education learning outcomes will turn out. Meanwhile, only physical education learning outcomes who influenced based on students’ school also this research that schools and teachers should promote healthy lifestyles and encourage students to always be active in supporting student achievement.